Hardening of the working tools of equipment for manufacturing fuel briquettes and pellets - Луцак, Д.Л.; Пилипченко, О.В.; Бурда, М.Й. (Problems of Tribology, 2015)
The article describes the list of factors experienced by working tools of equipment for manufacturing wood bri-quettes and pellets during exploitation, scheme of frictional interaction in pair of «pressed sawdust -steel» and a list of mate-rials and technologies used for hardfacing of the working tools of the mentioned equipment. The authors offer to apply acety-lene-oxygen method of coating «relit» on the working surfaces for more effective protection of quick-wear parts of briquet-ting presses, including screw extruders. Those coatings are characterized with high wear resistance against strong abrasive ef-fect